Molecular Mechanisms of Stem/Progenitor Cell Maintenance in the Adrenal Cortex - Lerario, Antonio Marcondes; Finco, Isabella; LaPensee, Christopher; Hammer, Gary Douglas (Frontiers in Endocrinology, 2017)
The adrenal cortex is characterized by three histologically and functionally distinct zones: the outermost zona glomerulosa (zG), the intermediate zona fasciculata (zF) and the innermost zona reticularis (zR). Important aspects of the physiology and maintenance of the adrenocortical stem/progenitor cells have emerged in the last few years. Studies have shown that the adrenocortical cells descend from a pool of progenitors that are localized in the subcapsular region of the zG. These cells continually undergo a process of centripetal displacement and differentiation which is orchestrated by several paracrine and endocrine cues, including the pituitary-derived adrenocorticotrophic hormone (ACTH), and angiotensin II. However, while several roles of the endocrine axes on adrenocortical function are well established, the mechanisms coordinating the maintenance of an undifferentiated progenitor cell pool with self-renewal capacity are poorly understood. Local factors such as the composition of the extracellular matrix (ECM) with embedded signaling molecules and the activity of major paracrine effectors including ligands of the sonic hedgehog and Wnt signaling pathways are thought to play a major role. Particularly, the composition of the ECM, which exhibits substantial differences within each of the three histologically distinct concentric zones, has been shown to influence the differentiation status of adrenocortical cells. New data from other organ systems and different experimental paradigms strongly support the conclusion that the interactions of ECM components with cell surface receptors and secreted factors are key determinants of cell fate. In this review, we summarize established and emerging data on the paracrine and autocrine regulatory loops that regulate the biology of the progenitor cell niche, and propose a role for bioengineered ECM models in further elucidating this biology in the adrenal.